Japan : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
KEY ISSUES Abenomics has lifted Japan out of the doldrums and needs to be reinforced to accomplish the desired 'once in a lifetime' economic regime shift. Building on initial positive results, policies now need to embark on a sustained effort to meet the unprecedented challenges Japan is facing: ending an entrenched deflationary mindset, raising growth, restoring fiscal and debt sustainability, and maintaining financial stability in the face of adverse demographics. Japan should be at the vanguard of structural reform. More vigorous efforts to raise labor supply and deregulate domestic markets, backed by further endeavors to raise wages and investment and designed to boost confidence and raise domestic demand, will be essential to lift growth, facilitate fiscal consolidation, and unburden monetary policy. A credible medium-term fiscal consolidation plan is needed to remove uncertainty about the direction of policies that may be holding back domestic demand. The overarching goal should be to put debt on a downward path, through gradual but steady consolidation that does not derail growth and inflation momentum. It should be based on prudent economic assumptions and on concrete structural revenue and expenditure measures identified upfront. More explicit monetary guidance would enhance inflation dynamics. Actual and expected inflation remain well below the Bank of Japan's (BoJ's) inflation target and monetary policy transmission remains weak. The BoJ needs to stand ready to undertake further easing and should provide stronger guidance to markets through enhanced communication. Absent deeper structural reforms, even with further easing, reaching two- percent inflation in a stable manner is likely to take longer than envisaged, suggesting that the BoJ should put greater emphasis on achieving the inflation target in a stable manner rather than within a specific time frame. The financial sector should be a greater catalyst for growth, and guard against risks from unconventional policies. The soundness of the financial system allows more risk taking and consolidation, while remaining resilient to the likely higher volatility of asset prices, exchange rates and interest rates, and lower liquidity in the JGB market as quantitative easing proceeds. While the 2014 external position was assessed to be broadly aligned with fundamentals, subsequent developments and incomplete policies raise the risk of negative spillovers. With the depreciation of the yen relative to its mid-2014 level, further monetary easing without bolder structural reforms and a credible medium-term fiscal consolidation plan could lead to sluggish domestic demand and overreliance on yen depreciation to pursue domestic policy objectives.